"My literature is in my letters" (literary and cultural discourseof epistolary by Vasyl Stefanyk) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The writer’s letters are considered in the article through the prism of his life writing and art works. It was proved that epistolary heritage is the key to the written laboratory of the novelist; genre and topical peculiarities of the letters are separated.
Keywords: letter; epistle; literature